Growth Mindset Moderates the Effect of the Neonatal Resuscitation Program on Performance in a Computer-Based Game Training Simulation - Maria Cutumisu; Maria Cutumisu; Maria Cutumisu; Matthew R. G. Brown; Caroline Fray; Georg M. Schmölzer; Georg M. Schmölzer (Frontiers Media S.A., 2018)
This study examines for the first time the moderating role of growth mindset on the association between the time elapsed since participants' last refresher neonatal resuscitation program (NRP) course and their performance on neonatal resuscitation tasks in the RETAIN computer game training simulation. Participants were n = 50 health-care providers affiliated with a large university hospital. Results revealed that growth mindset moderated the relation between participants' task performance in the game and the time since their latest refresher NRP course. Specifically, participants who completed the course more recently (i.e., between 8 and 9 months before the current study) made significantly more mistakes in the game than the rest of the participants but only when they endorsed lower levels of growth mindset. Implications of this research include growth mindset interventions and increased screen time in simulation sessions that have the potential to help health-care providers achieve better performance on neonatal resuscitation clinical tasks.